Catchment Size to Effective Tank Volume Relationships for Individual Lot Stormwater Detention System in Malaysian Detached House - Mah, D.Y.S.; Ngu, J.O.K.; Caroline, P.D.; Malek, M.A. (The World Academy of Research in Science and Engineering, 2020)
This paper describes an individual lot stormwater detention system that consists of multiple precast concrete modular green pavement units, developed by the authors. The tank size is determined at 4.40 m W, 4.70 m L and 0.45 m D with an effective tank volume of 3.93 m3 after being filled with the said modular units. The small tank size allows the system to be inserted into a residential house’s car porch. Maintaining the same tank size, exploration into different catchment sizes that drain water to the tank is carried out using two model intermediate and corner double-storey detached houses. The investigation is intended to figure out the optimum catchment size that could achieve the lowering of peak runoff caused by post-development condition to near pre-development condition. A computer model using Storm Water Management Model version 5.0 is developed to simulate scenarios of 40:60, 50:50 and 60:40 representing the contributing to non-contributing catchment ratios for intermediate and corner lots. Analysis of the simulation results show that 65% of the property lot designated as contributing catchment would contribute to achieve the desired pre-development condition.